High mirror symmetry in mouse exploratory behavior - Fonio, Ehud; Feinerman, Ofer (Frontiers in Behavioral Neuroscience, 2024)
Behavior can be considered as the subspace that remains after secluding all actions that are not available to the animal due to constraints. The physicality of the world in which the animal operates, its anatomical structure, physiology, perception, emotional states, and cognitive capabilitiesall determine the statistical boundaries of the behavioral space within which the animal can operate. The very signature of being a certain creature is reflected in these limitations that shape its behavior. A major goal of ethology is to expose those constraints that carve the intricate structure of animal behavior and reveal both uniqueness and commonalities between animals within and across taxa. Exploratory behavior in an empty arena seems to be stochastic, nevertheless, it does not mean that the animal is a random walker. In this paper, we present how adding constraint one can retain the 'mousiness' that characterizes the behaving mouse. We then introduce intriguing high mirrorsymmetry along the animals' locomotion which highlights a novel constraint that further compresses the complex nature of exploratory behavior in these mice. We link these findings to a known neural mechanism that could explain this phenomenon. Finally, we suggest our novel finding and derived methods to be used in the search for commonalities in the motion trajectories of various organisms across taxa.